2019
DOI: 10.3390/biomimetics4020041
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Antimicrobial Action of Surface Modified Magnesium Hydroxide Nanoparticles

Abstract: Magnesium hydroxide nanoparticles (Mg(OH)2NPs) have recently attracted significant attention due to their wide applications as environmentally friendly antimicrobial nanomaterials, with potentially low toxicity and low fabrication cost. Here, we describe the synthesis and characterisation of a range of surface modified Mg(OH)2NPs, including particle size distribution, crystallite size, zeta potential, isoelectric point, X-ray diffraction (XRD), dynamic light scattering (DLS), scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 51 publications
2
42
0
Order By: Relevance
“…Research studies have been determined that nano materials can be applied in functional composites, catalysts, sensors, semiconductors, microelectronics and as well, medical use 39 . In this context, the development of biocompatible magnesium hydroxide nanoparticles (Mg(OH) 2 NPs) as potent antibacterial and antifungal agents have been attracted great interests of scientists 40 . These nano-scale particles can be efficiently used in pharmaceutical formulations 41 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Research studies have been determined that nano materials can be applied in functional composites, catalysts, sensors, semiconductors, microelectronics and as well, medical use 39 . In this context, the development of biocompatible magnesium hydroxide nanoparticles (Mg(OH) 2 NPs) as potent antibacterial and antifungal agents have been attracted great interests of scientists 40 . These nano-scale particles can be efficiently used in pharmaceutical formulations 41 43 .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different NPs such as Au NPs, silica NPs, Mg(OH) 2 NPs and CuONPs have all been shown to demonstrate increased toxicity towards bacteria. [20][21][22][23][24]45 AgNPs has been researched in anti-biofilm treatments due to the silver ions intrinsic antimicrobial property. 25,43 Nanocarriers for antimicrobial agents have also been shown to increase their efficacy against a wide range of microorganisms, including resistant species [26][27][28][29] and deliver drugs specifically to a bacterial target.…”
Section: Introductionmentioning
confidence: 99%
“…The data from several previous studies indicated that nano-particle size is a key parameter for maximal antimicrobial activity and smaller particles cause further penetration into the microbial cell. 23,24 In the present study, zataria NEO droplets had a mean diameter of 61.5 nm, which seems to provide considerable penetration of droplets throughout the microbial cell wall. In this research, the MIC and MBCs of zataria EO and NEO were lower than those of Masoomi et al, indicating 2.5 mg/mL.…”
Section: Discussionmentioning
confidence: 49%